Potencial antiproliferativo, genotóxico e fitoquímica de Richardia brasiliensis Gomes - Dornelles, Rafaela Castro (2015)
The use of medicinal plants in therapy has developed over the years concurrently with the humanity evolution. With the difficulty of access to synthetic drugs, the rich plant biodiversity and the adverse economic situation that represents an obstacle to the use of traditional drugs, make the use of medicinal plants one of the main forms of therapeutic resource used by the population. In this way, studies reporting the effects of medicinal plants in living organisms, the standardization and determination of plants's quality are essential for a safe and effective use of it. The medicinal plant Richardia brasiliensis Gomes is known as white ipecac and is inserted in the Rubiaceae family, native to South America and foundin in tropical and subtropical regions. Secondary metabolites, such as volatile oils, sterols, alkaloids, tannins, flavonoids and coumarins this plant has important pharmacological activities in the treatment of diabetes, hemorrhoids and skin disease. Also, it is reported as having anthelmintic and anti-emetic actions. This study aimed to determine the vegetable parameters of quality, identify and quantify secondary metabolites, analyze the histochemistry of leaves and stems and evaluate the antiproliferative and genotoxic capacity of extracts and fractions at different concentrations on the cell cycle of Allium cepa L. R. brasiliensis was collected on the UFSM campus, in different seasons. The establishment of quality parameters and the obtainment of the extract by maceration were made from the plant drug powder. The extraneous material, percentage of water, swelling index and total and acid insoluble ash were determined by analyzing the plant material. The results showed that our findings are in line with the values recommended by the Brazilian Pharmacopoeia, although the ash contended have been high when compared to other species. The autumn extract had the highest yield (20.44%), and highest concentration of flavonoids (28.9 mg/g) as quantified by spectrophotometer. Rutin and chlorogenic acid were identified by HPLC-DAD and the highest concentration of rutin (26.25 mg/g) was in the autumn extract. Anthocyanin glycosides, tannins, amino groups, steroids and/or triterpenes, alkaloids, coumarins, organic acids and flavonoids have been reported through the characterization reactions. From the histochemistry of leaves and stems, it was determined the presence of storing and structural lipids, as well as phenolic compounds, anthocyanins and alkaloids. From the Allium cepa test concentrations of 10 and 500 μg/mL and positive, negative and diluent controls, it was possible to determined the genotoxicity and antiproliferative capacity of the plant. The crude extract of autumn and the butanol fraction at a concentration of 500 μg/mL had the lowest mitotic index (5.42 and 6.75% respectively). The extracts and fractions showed low number of altered cells (binucleated cells, micronucleus, disorganized chromosomes, chromosomes bridges and break) when compared to the positive control (glyphosate 1%).